2016
DOI: 10.1002/jrs.4918
|View full text |Cite
|
Sign up to set email alerts
|

A vibrational and conformational characterization of arginine at different pH values investigated using Raman spectroscopy combined with DFT calculations

Abstract: In the present study, the Raman spectra of an aqueous solution of arginine (Arg) at three different pH values (2.0, 9.0, and 10.5) were recorded in the spectral range 500-1800 cm À1 by using an excitation wavelength of 514 nm. The wavenumber position and intensity of the Raman bands lying in the spectral range 1000-1500 cm À1 changed with pH. The change in the peak parameters with pH was mainly attributed to the change of the molecular structure to zwitterionic (ZW), cationic zwitterionic (CATZW), or protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…The amide I vibration has been found to be heavily dependent on the formation of intramolecular hydrogen bonds in proteins, and hydrogen bonds, in turn, are integral in the stabilization of various protein secondary structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. As a result, vibrational spectroscopy combined with density functional theory (DFT) computations is commonly employed to investigate the molecular geometries, dynamics, and secondary structures of short peptide chains [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Navarette and coworkers reported the Raman and IR vibrational spectra for l -glutamic acid [ 44 ], l -aspartic acid (D) [ 35 ], and the glutamic acid (EE) and aspartic acid (DD) dipeptides [ 35 ] in their seminal works and found that these molecules are zwitterio...…”
Section: Introductionmentioning
confidence: 99%
“…The amide I vibration has been found to be heavily dependent on the formation of intramolecular hydrogen bonds in proteins, and hydrogen bonds, in turn, are integral in the stabilization of various protein secondary structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. As a result, vibrational spectroscopy combined with density functional theory (DFT) computations is commonly employed to investigate the molecular geometries, dynamics, and secondary structures of short peptide chains [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Navarette and coworkers reported the Raman and IR vibrational spectra for l -glutamic acid [ 44 ], l -aspartic acid (D) [ 35 ], and the glutamic acid (EE) and aspartic acid (DD) dipeptides [ 35 ] in their seminal works and found that these molecules are zwitterio...…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3d illustrates the HR (thick) and Raman (dotted) spectra of Arg. Table 4 lists the band assignments, [ 51–53 ] and the name of each atom in the side chain is presented in Scheme 1b. The HR bands at 1,415 and 1,369 cm −1 are assignable to the modes including ν s (COO − ).…”
Section: Resultsmentioning
confidence: 99%
“…Arginine possesses two proton donor groups (OH and NH), six proton acceptor sites (N and O), and six or seven bonds enabling molecular rotations. Accordingly, a number of different tautomers and conformers, including hydrated, 98 , 99 protonated, 100 and alkali-cationized 101 , 102 structures, are possible upon stabilization by different intermolecular hydrogen bonds. 98 The present Raman experiments suggest that the 935 cm –1 (N–C–N symmetric stretching) Raman fingerprint of the guanidinium group can be taken as a marker for strain infectivity and viral inactivation upon deimination.…”
Section: Discussionmentioning
confidence: 99%